Norman Podhoretz papers - Podhoretz, Norman
Correspondence, memoranda, diary, journal, writings, speeches, transcipts of interviews, newspaper clippings, printed matter, and other papers relating primarily to Podhoretz's career as author and editor of Commentary, New York, N.Y. Reflects his political transition from advocate of left-wing liberal ideology to leading spokesman for neoconservative philosophy. Includes correspondence, research materials, and drafts for Podhoretz's literary, social, and political criticism published in articles, short stories, and books. Subjects include censorship, the Middle East, military readiness, politics, social and cultural issues such as poverty and racism, travels to Asia, Australia, and India in the 1970s and 1980s, and the Vietnamese conflict. Also includes material concerning Saul Bellow; Albert Camus; Benjamin Disraeli, Earl of Beaconsfield; F.R. Leavis; and Edmund Wilson. Correspondents include Eldridge Cleaver, Midge Decter, Allen Ginsberg, Lillian Hellman, Daniel P. Moynihan, Susan Sontag, Terry Southern, Diana Trilling, Lionel Trilling, and Kurt Vonnegut.
Author and editor. Born 1930.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Bellow, Saul; Camus, Albert, -- 1913-1960.; Cleaver, Eldridge, -- 1935-1998 -- Correspondence; Decter, Midge -- Correspondence; Disraeli, Benjamin, -- 1804-1881.; Ginsberg, Allen, -- 1926-1997 -- Correspondence; Hellman, Lillian, -- 1905-1984 -- Correspondence; Leavis, F. R. -- 1895-1978.; Moynihan, Daniel P. -- 1927-2003 -- Correspondence; Sontag, Susan, -- 1933-2004 -- Correspondence; Southern, Terry -- Correspondence; Trilling, Diana -- Correspondence; Trilling, Lionel, -- 1905-1975 -- Correspondence; Vonnegut, Kurt -- Correspondence; Wilson, Edmund, -- 1895-1972.; Commentary (New York, N.Y.); American literature; American periodicals; Censorship; Conservatism; Criticism; Liberalism; Military readiness; Poverty; Racism; Vietnam War, 1961-1975.; Asia -- Description and travel; Australia -- Description and travel; India -- Description and travel; Middle East -- History; New York (N.Y.) -- Intellectual life -- 20th century; United States -- Intellectual life -- 20th century; United States -- Politics and government -- 20th century; United States -- Social conditions -- 20th century; Authors; Editors